A chromatin structure‐based model accurately predicts DNA replication timing in human cells. Issue 3 (28th March 2014) - Gindin, Yevgeniy; Valenzuela, Manuel S; Aladjem, Mirit I; Meltzer, Paul S; Bilke, Sven
Synopsis <boxed-text content-type="graphic" id="msb134859-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> A mechanistic model predicts cell lineage‐specific DNA replication timing based on the location of DNase‐hypersensitivity data alone. With essentially no parameters to adjust for different cell types, the model is truly predictive even for cells where timing data are not available. The mechanistic model predicts replication timing in human cells with an accuracy approaching the limit set by experimental noise. In the model, the timing program results from purely time‐stochastic initiation at well‐localized initiation sites and it is determined by the location of initiation sites alone regardless of initiation probabilities. Replication initiation sites are optimally localized by DNase‐hypersensitive sites.